2011
DOI: 10.2527/jas.2010-3704
|View full text |Cite
|
Sign up to set email alerts
|

Corn distillers dried grains with solubles in diets for growing-finishing pigs: A cooperative study1,2

Abstract: An experiment involving 560 crossbred pigs (28 replications of 4 to 6 pigs per pen) was conducted at 9 research stations to assess the effects of dietary concentrations of corn distillers dried grains with solubles (DDGS) on pig performance and belly firmness. Fortified corn-soybean meal diets containing 0, 15, 30, or 45% DDGS were fed in 3 phases from 33 to 121 kg of BW. A common source of DDGS containing 90.1% DM, 26.3% CP, 0.96% Lys, 0.18% Trp, 9.4% crude fat, 34.6% NDF, 0.03% Ca, and 0.86% P was used at ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
55
3
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(70 citation statements)
references
References 12 publications
(10 reference statements)
11
55
3
1
Order By: Relevance
“…As expected, feeding ingredients high in UFA increased carcass fat IV, which agrees with numerous other publications (Benz et al, 2010(Benz et al, , 2011Cromwell et al, 2011). In Exp.…”
Section: Methodssupporting
confidence: 82%
“…As expected, feeding ingredients high in UFA increased carcass fat IV, which agrees with numerous other publications (Benz et al, 2010(Benz et al, , 2011Cromwell et al, 2011). In Exp.…”
Section: Methodssupporting
confidence: 82%
“…However, Whitney et al (2006) and Linneen et al (2008) reported the Effects of conjugated linoleic acid/betaine on pig decreased growth performance as the increased concentration of dietary DDGS. The research including hundreds of pigs showed that 30% or 45% DDGS in diets reduced the ADG, but did not affect the ADFI or G : F (Cromwell et al, 2011). The possible reasons for these conflicting observations may be that the DDGS used in the experiments was poorer quality (less nutrient digestibility) than expected.…”
Section: Growth Performancementioning
confidence: 95%
“…In the current study, the IV of the backfat and belly fat increased in pigs fed diets containing 300 g DDGS/kg, which agrees with previous reports (Benz et al, 2010;Dahlen et al, 2011), indicating that the IV of fat increased with increased DDGS content in grower-finisher pig diets. Regression analysis in the research has hundreds of pigs indicated that IVs increased 4.3 units for every 10 percentage unit inclusion of DDGS in the diet (Cromwell et al, 2011). For backfat, the percentages of C18:0 and SFA were significantly increased (P < 0.05), but the percentages of C18:2, C18:3, C20:1, C20:3, PUFA and IV were decreased (P < 0.05) by the DDGS + CLA compared with the DDGS group.…”
mentioning
confidence: 98%
“…A maximum IV has not been universally accepted by the pork industry. However, a range from 70 to 74 has been recommended to be a maximum value (Boyd et al 1997;Cromwell et al 2011). In this experiment, no difference in fatty acid composition and IV of jowl and belly fat was observed.…”
Section: Fatty Acid Composition and Iodine Value Of Jowl And Belly Fatmentioning
confidence: 57%